Higher-Order Thinking Skills in Islamic Education Using SEM: The Role of Flipped Classroom Readiness and Ethno-Religious Value Integrity - Supriadi, Udin; Islamy, Mohammad Rindu Fajar; Parhan, Muhamad; Islamy, Muhammad Ruqy Faishal; Khosihan, Aan (Jurnal Pendidikan Agama Islam, 2026)
Purpose – This study investigates how culturally rooted value systems interact with digital pedagogical models to enhance Higher-Order Thinking Skills (HOTS) among students of Islamic education. It proposes an integrated cultural–pedagogical model examining the relationships among flipped classroom readiness (KFC), ethnoreligious value integrity (INE), hybrid problem-based learning (HPBL), and HOTS in Indonesian higher education. Design/methods/approach – A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 772 students using a validated 48-item questionnaire and analyzed using Structural Equation Modeling (SEM). To contextualize the model theoretically, a complementary bibliometric analysis of 1,387 Scopus-indexed publications on HOTS and digital pedagogy was conducted. Findings – The structural model demonstrated excellent fit (CFI = .961; RMSEA = .050) and explained 68% of the variance in HOTS. Results revealed that flipped classroom readiness significantly influenced hybrid problem-based learning (β = .58) and ethnoreligious value integrity (β = .52). However, flipped classroom readiness had no significant direct effect on HOTS (β = .09, p = .078). Instead, HOTS development was fully mediated through hybrid problem-based learning (β = .30) and ethnoreligious value integrity (β = .15). Research implications/limitations – The findings suggest that digital learning readiness alone is insufficient to foster HOTS without culturally grounded mediation. However, the study is limited to Islamic education students in Indonesia. Originality/value – This study offers a novel cultural–pedagogical model integrating digital learning readiness, ethnoreligious values, and hybrid problem-based learning, providing new insights for culturally responsive curriculum design in Islamic higher education.